Corporate Social Responsibility 2022
DOI: 10.5772/intechopen.94344
|View full text |Cite
|
Sign up to set email alerts
|

CSR and Innovation: Two Sides of the Same Coin

Abstract: In this chapter, we analyze the association between CSR and innovation. We state that CSR concept has evolved over time and has changed the way innovation is conceived. The state of art shows that CSR activities have been responsively introduced to achieve the stakeholders’ needs and standards, to become gradually more strategic activities. In fact, many firms have been involved in CSR projects dealing with the reputation enhancement, the stakeholders’ reciprocation, the risk mitigation, and the improvement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Hlioui and Yousfi (2020) contended that CSR forms a trajectory for evolving changes and innovation influenced by the managerial perspectives. However, the social commitment of the manager is influenced by institutional framework.…”
Section: Discussionmentioning
confidence: 99%
“…Hlioui and Yousfi (2020) contended that CSR forms a trajectory for evolving changes and innovation influenced by the managerial perspectives. However, the social commitment of the manager is influenced by institutional framework.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the business plan elaboration could considerably affect the credit constraints and innovation link. Hlioui and Yousfi [43], underlined the importance of busi-ness plan elaboration, especially for sustainable practices integration and responsible innovation. They indicated that formalized business plans should integrate sustainable strategies and that they could moderate the financial obstacles and innovation relationship.…”
Section: The Conditional Mediation Of Credit Access On the Informal C...mentioning
confidence: 99%
“…To test our second stage-moderated-mediation, we consider the elaboration of a formalized written business plan as an important variable that moderates the credit constraints innovation link. According to Hlioui and Yousfi [43], the corporate business plan could influence significantly corporate innovation, CSR and financial resources link. In the same line, Cosci et al [10] underlined that the bank's evaluation of the companies' business plans while assessing creditworthiness fosters innovation.…”
Section: Second Stage Moderatormentioning
confidence: 99%
“…Ref. [70] highlight the dynamic between strategic CSR activities and innovation mechanisms. This dynamic lets firms improve their social performance and competitiveness.…”
Section: The Moderating Effect Of Innovationmentioning
confidence: 99%